Pengaruh Faktor-Faktor Budaya Organisasi Terhadap Kinerja Pegawai Dinas Ketahanan Pangan dan Pertanian Kabupaten Bojonegoro - Arbaatun, Yunia; Soedarto, Teguh (Universitas Bojonegoro, 2022)
Employee culture and performance is a central topic in the development of human resources in the future. Employee performance problems are indeed a major problem in an organization. Therefore, the Bojonegoro Regency Agriculture Service needs to first identify the variables that affect employee performance, the extent of their influence so that it has an impact on performance.. Performance in the organization is inseparable from the existence of its organizational culture, a weak culture will interfere with organizational activities to achieve its goals. This research is about the influence of organizational culture in the perspective of differentiation, integration perspective and fragmentation perspective on employee performance at the Department of Agriculture of Bojonegoro Regency. These three perspectives affect employee performance together by 44.7%, while the remaining 55.3% employee performance is influenced by other than organizational culture. Organizational culture factors which include differentiation perspective, integration perspective and fragmentation perspective partially have no significant effect on employee performance. Meanwhile, the organizational culture factor of the integration perspective has a dominant influence on the performance of the employees of the Department of Agriculture, Bojonegoro Regency, East Java Province.